THE EFFECT OF GLOBALIZATION ON CULTURE, INFORMATION TECHNOLOGY, AND EDUCATION - Inggis Mialiawati (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
Globalization is the most important factor in driving indicators of the rate of change of a country. If a country has good indicators of globalization, this is a positive point for that country. However, the rate of globalization is not accompanied by appropriate norms in society, causing an imbalance in the nation and state, which clearly influences norms in life. This research was written to learn how globalization affects culture, information technology, and education. The research method used is a qualitative method with interview techniques to 20 student of UNISRI`s Civic Education Program, who aged 18-20 years. The results showed that on average, a total of 80% of students saw and felt the effects of globalization. Then it must be provided with supervision by parents and increase information about the impact of globalization on culture, information technology, and education which is also very influential on learning so that it can provide great motivation for people to read and learn information from various sources and can protect themselves from carried by the very strong currents of globalization. Keywords: Globalization, Culture, Information Technology, and Education.